Exploration of the Antimicrobial and Catalytic Properties of Gold Nanoparticles Greenly Synthesized by Cryptolepis buchanani Roem. and Schult Extract - Kamonpan Wongyai (Journal of Nanomaterials, 2020)
A green, simple, and rapid synthesis of gold nanoparticles using plant extract, Cryptolepis buchanani Roem. and Schult, and their applications are first described in this paper. The formation of gold nanoparticles was visually observed by the appearance of a ruby red color, which was further indicated by an absorption peak at 530 nm in UV-Vis spectroscopy. Optimization of reaction parameters for the gold nanoparticles was also investigated. Various analytical techniques were employed as part of the process of characterizing the resulting gold nanoparticles. Fourier transform infrared (FTIR) analysis revealed that the phenol compounds present in the extract were responsible for gold(III) reduction and stabilization of gold nanoparticles. Transmission electron microscopy (TEM) analysis showed that the gold nanoparticles were spherical in shape with an average diameter of 11 nm. Powder X-ray diffraction (XRD) pattern indicated that the green synthesis approach produced highly crystalline, face-centered cubic gold nanoparticles. Energy-dispersive X-ray spectroscopy (EDS) measurements confirmed the presence of elemental gold in the prepared nanoparticles. The negative zeta potential value of gold nanoparticles was found to be -30.28 mV. The green synthesized gold nanoparticles expressed effective antibacterial activity against Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, and Acinetobacter baumannii and exhibited an excellent catalytic property in terms of its reduction ability of methylene blue.